IMPORTANT FACTORS FOR FORMATION OF SOCIAL ACTIVITY SKILLS IN STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS (Spectrum Journal of Innovation, Reforms and Development, 2022)
This article examines the role of motivation and motivation in the formation of social activity skills in students and the importance of their application in practice on a scientific basis.